THE EFFECT OF FIRM SIZE AND LEVERAGE ON FINANCIAL PERFORMANCE AND THEIR IMPACT ON FIRM VALUE IN FOOD AND BEVERAGE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Asep Saepul Bahri; Kurniawan Saefullah; Mokhamad Anwar (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
The current state of the world economy is in decline, including in Indonesia due to the Covid-19 outbreak, which has affected almost all economic sectors. However, several food and beverage companies listed on the Indonesian stock exchange have remained stable, if not rising, as if they will be unaffected by the outbreak of Covid 19 the purpose of this research was to investigate the impact of business size and leverage on financial performance and firm values. From 2017 to 2020, this study used a sample of food and beverage firms listed on the Indonesia Stock Exchange (IDX). The information used was gathered from a panel of people. Path analysis is the data analysis technique that was used.Firm size has a significant effect on financial performance, leverage has a significant effect on financial performance, firm size has a significant effect on firm value, leverage has insignificant effect on firm value, financial performance has a significant effect on firm value, and financial performance can mediate firm size and leverage, according to the findings of the study.